Government Ponzi Games and Debt Dynamics Under Uncertainty - Bartolini, Leonardo (IMF Working Papers; Working Paper ;, 1991)
We investigate the conditions for sustainability of debt roll-over schemes under uncertainty. In contrast with the requirements identified in recent research, we show that a necessary and sufficient condition for sustainability of such schemes is that the asymptotic interest rate on government debt be lower than the asymptotic growth rate of the economy, a natural extension of a familiar criterion in a deterministic framework. However, we also show that for realistic parameter values, Ponzi games that are sustainable in the long run may display explosive patterns over relatively long horizons. This may explain why governments may be reluctant to play Ponzi games even when they are feasible in the long run.